Electroacupuncture Attenuates Cerebral Ischemia and Reperfusion Injury in Middle Cerebral Artery Occlusion of Rat via Modulation of Apoptosis, Inflammation, Oxidative Stress, and Excitotoxicity - Mei-hong Shen (Evidence-Based Complementary and Alternative Medicine, 2016)
Electroacupuncture (EA) has several properties such as antioxidant, antiapoptosis, and anti-inflammatory properties. The current study was to investigate the effects of EA on the prevention and treatment of cerebral ischemia-reperfusion (I/R) injury and to elucidate possible molecular mechanisms. Sprague-Dawley rats were subjected to middle cerebral artery occlusion (MCAO) for 2 h followed by reperfusion for 24 h. EA stimulation was applied to both Baihui and Dazhui acupoints for 30 min in each rat per day for 5 successive days before MCAO (pretreatment) or when the reperfusion was initiated (treatment). Neurologic deficit scores, infarction volumes, brain water content, and neuronal apoptosis were evaluated. The expressions of related inflammatory cytokines, apoptotic molecules, antioxidant systems, and excitotoxic receptors in the brain were also investigated. Results showed that both EA pretreatment and treatment significantly reduced infarct volumes, decreased brain water content, and alleviated neuronal injury in MCAO rats. Notably, EA exerts neuroprotection against I/R injury through improving neurological function, attenuating the inflammation cytokines, upregulating antioxidant systems, and reducing the excitotoxicity. This study provides a better understanding of the molecular mechanism underlying the traditional use of EA.